Macro and Micro-Vascular Complications and their Risk Factors in Diabetes Mellitus Patients of Southern Punjab, Pakistan - Hassan Gillani, Ali; Bashir, Sadia; Ahmed, Abu Bakar; Usman, Muhammad; Mustafa, Asim; Iqbal, Taha; Batool, Narjis (Journal of Pharmacy Practice and Community Medicine)
Background: Diabetes is defined as syndrome and is accompanied by number of micro and macro-vascular complications. The burden is quite high in developing countries so the main aim of this study is to evaluate complications in diabetes patients of Pakistan. Methods: A cross-sectional descriptive study was undertaken from December 2015 to March 2016 using a paper based questionnaire. Patients were selected from the 3 private clinics and 3 hospitals employing the systematic sampling technique and anthropometric readings were taken for each individual. The complications were measured by the standards measuring procedures. The demographics were elaborated by the descriptive statistics and the binary logistic regression model was used to analyze the factors associated with the complications by using SPSS version 18. Results: Mean age± SD of the respondent’s was 48.8±14.6 year. One hundred and thirty (43.5%) were females, 270 (90.3%) were married, 103 (34.5%) were rural resident, 189 (63.2%). Sixty five (21.7%) patients accompany Cardiovascular disease (CVD), 51 (17.0%) had diabetic nephropathy, 96 (32.1) had diabetic neuropathy and 124 (41.5%) had diabetic retinopathy. Age (AOR=2.477 95%CI=1.085, 5.654, p=0.031) and abnormal blood glucose level (AOR=1.872 95%CI=1.005, 3.487, p=0.048) is the significantly affecting factors of CVD. Body mass index was the strongest independent predictor for diabetic nephropathy (AOR=0.233 95%CI=0.067, 0.806, p=0.021) and diabetic retinopathy (AOR=3.558 95%CI=1.884, 6.719 p=0.00). Conclusion: The complications seem to be high among the diabetic patients with high frequency of the risk factors accompanying them. Imparting appropriate knowledge and preventing strategies will prove to be of immense benefits in reducing the co-morbidities.
Keywords: Micro-Vascular complications; Macro-Vascular complications; Diatbetes; Pakistan